PENGARUH DISIPLIN KERJA TERHADAP KINERJA GURU PADA SMAN 1 CANDUANG KABUPATEN AGAM - Husna, Nikmatul (Jurnal Ekobistek, 2017)
The purpose of this research is to identify and analyze the influence of work disciplinary towards teachers? performances in SMAN 1 Canduang Kabupaten Agam. The population of the research is the teachers in SMAN 1 Canduang Kabupaten Agam. Samples taken are 35 respondents by using census technique, which is a technique to determine sample by selecting data from all population and using quetionnaire as data collecting tool. Based on hypotheses in this research, it is assumed that work disciplinary has positive and significant impact toward teachers? performance in SMA N 1 Canduang Kabupaten Agam.The methods that author used in this research are validity test, reliability test, variable descriptive analysis, simple linear regression analysis, T test and F test. From the analysis that has been conducted, author found that the work disciplinary variable has positive and significant impact to teachers? performance, that has been proven by the significant probability value 0,007 which is smaller than 0.05. Then, from the result of F test, it can be concluded that the regression model can be used to predict that the work disciplinary has positive and significant impact on teachers? performance that is equal to 0.007, which is much smaller than 0.05.Keywords : work disciplinary, teachers? performance